Preparation method of copper nanorod
Through ultrasonic-assisted hydrothermal method, combined with solid-liquid separation, washing, drying and calcining steps, rod-shaped nano-copper oxide with high aspect ratio was prepared, which solved the problems of low purity of copper oxide and uneven size distribution in traditional methods, and achieved an efficient and controllable preparation process.
Patent Information
- Application Number
- CN202411737640.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
AI Technical Summary
When preparing copper oxide by traditional hydrothermal method, the purity is low and the size distribution is uneven, making it difficult to control.
Using an ultrasonic-assisted method, the copper salt is arranged as an aqueous solution of copper precursor, and mixed with an alkaline mixed solution to undergo hydrothermal reaction, followed by solid-liquid separation, washing, drying and calcination to obtain rod-shaped nano copper oxide with high aspect ratio.
The high yield of copper oxide is achieved, the purity of copper oxide powder is improved, and the problem of uneven size distribution is solved.
Smart Images

Figure CN119569100A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of metal powder nanomaterial preparation, and in particular to a method for preparing copper nanorods. Background Art
[0002] In the traditional hydrothermal method for preparing copper oxide, although it has the advantages of simple process, low energy consumption, high product purity and high yield; however, the copper oxide obtained by this method is difficult to control in terms of particle purity, crystal growth, morphology and size, resulting in low purity of the prepared copper oxide and uneven size distribution of the copper oxide.
[0003] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0004] In view of this, a method for preparing copper nanorods is provided, thereby overcoming, at least to some extent, the problems of low purity of copper oxide and uneven size distribution of copper oxide caused by limitations and defects of related technologies.
[0005] According to one aspect of the present disclosure, a method for preparing copper nanorods is provided, the method comprising the following steps:
[0006] Step 1: preparing a copper salt into a copper precursor aqueous solution, and preparing a base into an alkaline mixed solution;
[0007] Step 2: adding the copper precursor aqueous solution to the alkaline mixed solution under the assistance of ultrasound to obtain a copper-mixed alkaline solution;
[0008] Step 3, transferring the copper-mixed alkali solution to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing copper compounds;
[0009] Step 4: solid-liquid separation, washing, drying and calcining of the nanoparticle solution containing copper compound to obtain copper oxide powder composed of rod-shaped nano copper oxide.
[0010] In an exemplary embodiment of the present disclosure, the copper salt includes at least one of copper chloride, copper acetate, copper sulfate and copper nitrate.
[0011] The concentration of the copper precursor aqueous solution is less than or equal to 70 g / L.
[0012] In an exemplary embodiment of the present disclosure, the alkaline mixed solution includes multiple ones of sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate and ammonia water, the concentration of the alkaline mixed solution is less than or equal to 150 g / L, and the pH value of the alkaline mixed solution is between 12 and 14, which is in a strong alkaline state.
[0013] In an exemplary embodiment of the present disclosure, the alkaline mixed solution includes any one of the following: a mixed solution of sodium hydroxide and sodium carbonate, a mixed solution of sodium hydroxide and sodium bicarbonate, a mixed solution of sodium hydroxide and ammonium carbonate, a mixed solution of sodium hydroxide and ammonium bicarbonate, and a mixed solution of sodium hydroxide and aqueous ammonia.
[0014] In an exemplary embodiment of the present disclosure, in an ultrasound-assisted scenario, the frequency of the ultrasound is less than or equal to 4 MHz;
[0015] In the process of adding the copper precursor aqueous solution into the alkaline mixed solution, the adding method adopted is any one of dripping, peristaltic pump injection and atomization spraying.
[0016] In an exemplary embodiment of the present disclosure, in the process of transferring the copper-mixed alkali solution to a polytetrafluoroethylene reactor for hydrothermal reaction, the temperature of the hydrothermal reaction is 100° C. to 200° C., and the duration of the hydrothermal reaction is 1 to 10 h;
[0017] During the process of transferring the copper-mixed alkali solution to the polytetrafluoroethylene reactor for hydrothermal reaction, the pressure in the polytetrafluoroethylene reactor is between 3 and 10 MPa.
[0018] In an exemplary embodiment of the present disclosure, in the process of solid-liquid separation of the nanoparticle solution containing a copper compound, the solid-liquid separation method includes centrifugal separation or suction filtration separation;
[0019] In the process of washing the copper-containing compound nanoparticles after solid-liquid separation, the washing solution used includes water or ethanol;
[0020] In the process of drying the washed copper compound-containing nanoparticles, the drying method used includes heat drying or cold drying;
[0021] In the process of calcining the dried copper-containing compound nanoparticles, the calcination temperature used is 200°C to 500°C.
[0022] In an exemplary embodiment of the present disclosure, during the process of calcining the dried copper-containing compound nanoparticles, the atmosphere used is air.
[0023] In an exemplary embodiment of the present disclosure, the copper nanorods are rod-shaped nano copper oxides with a high aspect ratio, the rod-shaped nano copper oxides with a high aspect ratio have a length of 5 to 10 μm, a diameter of 30 to 60 nm, and an average aspect ratio of 100 to 200:1.
[0024] In an exemplary embodiment of the present disclosure, rod-shaped nano copper oxide with a high aspect ratio is used to prepare electronic devices and / or sensors.
[0025] In a method for preparing copper nanorods provided in an exemplary embodiment of the present disclosure, a copper salt is configured as a copper precursor aqueous solution, and an alkali is configured as an alkaline mixed solution; then, under the assistance of ultrasound, the copper precursor aqueous solution is added to the alkaline mixed solution to obtain a copper-mixed alkali solution; the copper-mixed alkali solution is then transferred to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing copper compounds; finally, the nanoparticle solution containing copper compounds is subjected to solid-liquid separation, washing, drying and roasting to obtain a copper oxide powder composed of rod-shaped nano copper oxide. Since the alkaline mixed solution can be used as a synergistic control agent for regulating the crystal nucleation growth of the copper nanorods, and the reaction kinetics during the crystal growth of the copper nanorods is regulated by changing factors such as the hydrothermal reaction temperature and reaction time, a high-yield and controllable preparation of rod-shaped nano copper oxide is achieved; on this basis, the purity of the obtained copper oxide powder is also improved, and the problem of uneven size distribution of the copper oxide powder is solved.
[0026] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0028] Figure 1 A flowchart of a method for preparing copper nanorods according to an exemplary embodiment of the present disclosure is schematically shown.
[0029] Figure 2 The SEM image of a rod-shaped nano-copper oxide with a high aspect ratio obtained based on Example 1 according to an exemplary embodiment of the present disclosure is schematically shown.
[0030] Figure 3The XRD (i.e., the spectrum of material structure analysis obtained by X-ray diffraction technology) diagram of a rod-shaped nano copper oxide with a high aspect ratio obtained based on Example 1 according to an exemplary embodiment of the present disclosure is schematically shown.
[0031] Figure 4 A SEM image of nano copper oxide obtained based on Comparative Example 1 according to an exemplary embodiment of the present disclosure is schematically shown.
[0032] Figure 5 A SEM image of nano copper oxide obtained based on Comparative Example 2 according to an exemplary embodiment of the present disclosure is schematically shown. DETAILED DESCRIPTION
[0033] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present disclosure will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted. In addition, the drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale.
[0034] The terms "a", "an", "the", "said" and "at least one" are used to indicate the presence of one or more elements / components / etc.; the terms "including" and "having" are used to express an open-ended inclusive meaning and mean that additional elements / components / etc. may exist in addition to the listed elements / components / etc.; the terms "first", "second" and "third" etc. are used merely as labels and are not intended to limit the quantity of their objects.
[0035] Copper oxide has the characteristics of large specific surface area, high chemical activity, high electron mobility, high thermal conductivity, strong adsorption capacity, strong selectivity, etc. On this basis, copper oxide also has special electrical, optical, catalytic and other excellent physical and chemical properties, and has a wide range of applications in the fields of redox catalytic reactions, lithium-ion batteries, energetic materials, gas sensors, printing and dyeing, glass, ceramics, and medicine. Therefore, with the development of these fields, higher and higher requirements are put forward for the morphology, size, activity, specific surface area and other structures of copper oxide powder.
[0036] In the process of practical application, nanomaterials have the characteristics of small particle size, large surface area, high surface energy and a large proportion of surface atoms compared to bulk materials; therefore, if nanomaterials are given some special effects, such as surface effect, small size effect, macroscopic quantum tunneling effect, quantum size effect, photoelectric effect, etc., the nanomaterials can exhibit more excellent physical and chemical properties.
[0037] In the past few decades of research, researchers have developed a series of methods for preparing copper oxide, such as vacuum condensation, physical vapor deposition, electrochemical method, spray drying, sol-gel method and hydrothermal method. Among them, the hydrothermal method has the advantages of simple process, low energy consumption, high product purity and high yield, so it has been widely used in actual production. However, the traditional hydrothermal method is difficult to control in terms of particle purity, crystal growth, morphology and size, resulting in low purity of the prepared copper oxide. At the same time, there is also the problem of uneven size distribution of copper oxide, so it is necessary to develop new strategies to regulate the nucleation and growth of copper oxide crystals.
[0038] Based on this, the exemplary embodiment of the present disclosure first provides a method for preparing copper nanorods. Specifically, refer to Figure 1 As shown, the method for preparing the copper nanorods may include the following steps:
[0039] Step S110. The copper salt is configured as a copper precursor aqueous solution, and the alkali is configured as an alkaline mixed solution;
[0040] Step S120. Under the assistance of ultrasound, adding the copper precursor aqueous solution to the alkaline mixed solution to obtain a copper-mixed alkaline solution;
[0041] Step S130. transferring the copper-mixed alkali solution to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing copper compounds;
[0042] Step S140: subjecting the nanoparticle solution containing the copper compound to solid-liquid separation, washing, drying and calcining to obtain copper oxide powder composed of rod-shaped nano-copper oxide.
[0043] In the above-mentioned method for preparing copper nanorods, the copper salt is configured as a copper precursor aqueous solution, and the alkali is configured as an alkaline mixed solution; then, under the assistance of ultrasound, the copper precursor aqueous solution is added to the alkaline mixed solution to obtain a copper-mixed alkali solution; the copper-mixed alkali solution is then transferred to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing copper compounds; finally, the nanoparticle solution containing copper compounds is subjected to solid-liquid separation, washing, drying and roasting to obtain a copper oxide powder composed of rod-shaped nano copper oxide. Since the alkaline mixed solution can be used as a synergistic control agent for regulating the crystal nucleation growth of the copper nanorods, and the reaction kinetics of the crystal growth process of the copper nanorods are regulated by changing factors such as the hydrothermal reaction temperature and reaction time, the high-yield and controllable preparation of rod-shaped nano copper oxide is achieved; on this basis, the purity of the obtained copper oxide powder is also improved, and the problem of uneven size distribution of the copper oxide powder is solved.
[0044] Hereinafter, the method for preparing copper nanorods described in the exemplary embodiment of the present disclosure will be further explained and illustrated in conjunction with the accompanying drawings.
[0045] First, the technical implementation principle of the exemplary embodiment of the present disclosure is explained and illustrated. Specifically, in the preparation method of copper nanorods recorded in the exemplary embodiment of the present disclosure, firstly, a copper salt aqueous solution and an alkaline mixed solution are prepared, and the two solutions are mixed with the assistance of ultrasound to create conditions for the nano-scale dispersion of copper salts and the regulation of crystal nucleation growth of copper nanorods; then, a hydrothermal synthesis method is used to optimize the reaction kinetic conditions of crystal growth by changing the reaction temperature, pressure and time, and nanoparticles containing copper compounds are obtained, and then after solid-liquid separation, washing, drying and roasting, they are decomposed to obtain rod-shaped nano copper oxide with a high aspect ratio, thereby achieving the regulation of the morphology and size of nano copper oxide; since a common water-soluble copper precursor can be used as a copper source, and an ordinary alkaline mixed solution can be used as a synergistic control agent for regulating crystal nucleation growth, the preparation cost of copper nanorods is reduced.
[0046] Secondly, Figure 1 The preparation method of the copper nanorods shown in the figure is further explained and illustrated. Specifically:
[0047] In step S110 , the copper salt is configured as a copper precursor aqueous solution, and the base is configured as an alkaline mixed solution.
[0048] Specifically, the copper salts recorded herein may include but are not limited to copper chloride, copper acetate, copper sulfate and copper nitrate, etc., and may also include a combination of copper chloride, copper acetate, copper sulfate and copper nitrate. In actual application, they can be selected according to actual needs, and this example does not impose any special restrictions on this; at the same time, the concentration of the copper precursor aqueous solution obtained based on this method needs to be controlled within 70g / L, that is, the concentration of the copper precursor aqueous solution needs to not exceed 70g / L.
[0049] Furthermore, the alkaline mixed solution described herein may include but is not limited to sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate and ammonia water, etc., and the concentration of the alkaline mixed solution is less than or equal to 150 g / L; at the same time, in a possible exemplary embodiment, the alkaline mixed solution includes any one of the following: a mixed solution of sodium hydroxide and sodium carbonate, a mixed solution of sodium hydroxide and sodium bicarbonate, a mixed solution of sodium hydroxide and ammonium carbonate, a mixed solution of sodium hydroxide and ammonium bicarbonate, and a mixed solution of sodium hydroxide and ammonia water; in another possible exemplary embodiment, the alkaline mixed solution may also include any one of the following: a mixed solution of sodium hydroxide, sodium carbonate and sodium bicarbonate, a mixed solution of sodium hydroxide, sodium carbonate and ammonium carbonate, a mixed solution of sodium hydroxide, sodium carbonate and ammonium bicarbonate, and a mixed solution of sodium hydroxide, sodium carbonate and ammonia water; in some other possible exemplary embodiments, the alkaline mixed solution may also be a mixed solution of sodium hydroxide and other alkaline solutions, etc., which can be selected according to actual needs during actual application.
[0050] It should be noted here that, in the actual application process, the reason why an alkaline mixed solution including sodium hydroxide needs to be configured is that the solubility of copper salts is low in high pH solutions, which can achieve the purpose of reducing the nucleation rate and growth rate, thereby facilitating the preferential growth of specific crystal faces; at the same time, by controlling the concentration of the copper salt aqueous solution, the type and concentration of the screened alkali, the purpose of satisfying the needs of the product nano-copper oxide nucleation growth and morphology size regulation can be achieved.
[0051] In step S120, under the assistance of ultrasonic waves, the copper precursor aqueous solution is added to the alkaline mixed solution to obtain a copper-mixed alkaline solution.
[0052] Specifically, in the ultrasonic-assisted scenario, the frequency of the ultrasonic wave is less than or equal to 4 MHz; in the process of adding the copper precursor aqueous solution to the alkaline mixed solution, the addition method adopted may include but is not limited to dripping, peristaltic pump injection, and atomization spraying, etc.; at the same time, the reason why a 4 MHz ultrasonic frequency is needed is that the ultrasonic wave at this frequency is conducive to the nano-scale dispersion and mixing of the copper salt aqueous solution and the mixed alkali solution, and also helps the transmission and diffusion of the copper salt and the regulation of the copper compound by the mixed alkali solution during the crystal growth process.
[0053] In step S130, the copper-mixed alkali solution is transferred to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing copper compounds.
[0054] Specifically, in the process of transferring the copper-mixed alkali solution to a polytetrafluoroethylene reactor for hydrothermal reaction, the temperature of the hydrothermal reaction is 100°C to 200°C, and the duration of the hydrothermal reaction is 1h to 10h; in the process of transferring the copper-mixed alkali solution to a polytetrafluoroethylene reactor for hydrothermal reaction, the pressure of the polytetrafluoroethylene reactor is between 3 and 10MPa. It should be noted here that the reason why the temperature of the hydrothermal reaction is set to 100°C to 200°C and the duration of the hydrothermal reaction is set to 1h to 10h is that temperature is an important factor in determining the growth rate of nanomaterials. Higher temperatures can increase the reaction rate, allowing the material to grow rapidly in a specific direction; at the same time, too high a temperature may cause nucleation to be too fast, resulting in irregular morphology. Therefore, reasonable control of temperature and reaction time can help form a uniform rod-like structure. The hydrothermal reaction temperature recorded in the exemplary embodiment of the present disclosure is conducive to slow nucleation and growth, and helps the longitudinal growth of copper compounds, thereby forming a rod-like structure. Furthermore, in a polytetrafluoroethylene reactor, the effect of temperature changes on pH is particularly significant; and during the chemical reaction process, the pH value in the reactor needs to be strictly controlled, because the increase in temperature will increase the ion product constant (Kw) of water, thereby increasing the concentration of hydrogen ions and hydroxide ions, thereby reducing the pH value. A slight change in pH value may affect the rate of chemical reactions and the properties of the products; during the reaction process, pressure will also affect the reaction rate and change the equilibrium constant of the chemical reaction. Under high pressure, the probability of collision between molecules increases, and the interaction is enhanced, thereby promoting the progress of chemical reactions. Therefore, in practical applications, the reaction temperature and pressure need to be strictly controlled to ensure the smooth progress of the reaction and the quality of the product.
[0055] In step S140, the nanoparticle solution containing the copper compound is subjected to solid-liquid separation, washing, drying, and calcining to obtain copper oxide powder composed of rod-shaped nano copper oxide.
[0056] Specifically, in the process of solid-liquid separation of the copper compound nanoparticle solution, the solid-liquid separation method includes centrifugal separation or suction filtration separation; in the process of washing the copper compound nanoparticles after solid-liquid separation, the washing solution used includes water or ethanol; in the process of drying the washed copper compound nanoparticles, the drying method used includes hot drying or cold drying; in the process of calcining the dried copper compound nanoparticles, the calcination temperature used is 200°C to 500°C; at the same time, in the process of calcining the dried copper compound nanoparticles, the atmosphere used is air.
[0057] At the same time, the copper nanorods prepared based on the above method are rod-shaped nano copper oxides with a high aspect ratio, and the rod-shaped nano copper oxides with a high aspect ratio have a length of 5 to 10 μm, a diameter of 30 to 60 nm, and an average aspect ratio of 100 to 200:1. In addition, the copper nanorods prepared based on the above method can be used to prepare electronic devices and / or sensors; further, since the rod-shaped copper oxide powder has the characteristics of a high aspect ratio, it can be endowed with the characteristics of high electronic conductivity and high reactivity, so it can be widely used in important fields such as electronic devices and sensors, so that the obtained electronic devices and sensors have the characteristics of high conductivity and high reactivity.
[0058] So far, the method for preparing the nano copper rods described in the exemplary embodiments of the present disclosure has been fully realized. Based on the above contents, it can be known that the method for preparing the nano copper rods described in the exemplary embodiment of the present disclosure has at least the following advantages: on the one hand, the exemplary embodiment of the present disclosure adopts a common water-soluble copper precursor as a copper source and a common alkaline mixed solution as a synergistic control agent for regulating the nucleation and growth of the crystal, thereby realizing the controllable preparation of the morphology of nano copper oxide and reducing the preparation cost of nano copper oxide; on the other hand, the exemplary embodiment of the present disclosure ultrasonically disperses the copper salt aqueous solution and the mixed alkaline solution, which is helpful for the transmission and diffusion of the copper salt and the regulation of the copper compound by the mixed alkaline solution during the crystal growth process; further, the exemplary embodiment of the present disclosure optimizes the reaction kinetic conditions of crystal growth by changing the reaction temperature, pressure, time and pH value of the reactor, so that the copper compound grows longitudinally, thereby realizing precise control of the morphology and size of the product copper-containing compound nanoparticles; finally, the exemplary embodiment of the present disclosure realizes precise control of the crystal structure, morphology and size of nano copper oxide by controlling the solid-liquid separation method, washing method, drying conditions and roasting method of the copper compound nanoparticles, which is helpful for obtaining rod-shaped nano copper oxide with a high aspect ratio.
[0059] Hereinafter, the water-based polytetrafluoroethylene coating and its preparation process described in the exemplary embodiments of the present disclosure will be further explained and illustrated in conjunction with specific embodiments. Specifically:
[0060] Example 1
[0061] The preparation method of this embodiment comprises the following steps:
[0062] Step 1, preparing copper acetate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and a mixed alkaline solution respectively; the concentration of the copper salt aqueous solution is 70 g / L, the concentration of sodium carbonate in the mixed alkaline solution is 100 g / L, the concentration of sodium hydroxide is 40 g / L, and the pH value of the mixed alkaline solution is between 12 and 14, which is in a strong alkaline state;
[0063] Step 2: Adding a copper salt aqueous solution to a sodium hydroxide-sodium carbonate alkaline mixed solution with the aid of a high-frequency ultrasonic dispersion device with a frequency of 4 MHz to prepare a copper-mixed alkaline solution;
[0064] Step 3: Transfer the copper-mixed alkali solution obtained in step 2 to a polytetrafluoroethylene reactor, adopt a hydrothermal synthesis method, the reaction temperature is 120° C., the pressure in the reactor is between 3 and 10 MPa, and after two hours, collect and obtain a nanoparticle solution containing copper compounds;
[0065] Step 4: centrifuge the copper compound nanoparticle solution collected in step 3, wash with 18.2MΩ ultrapure water, dry in an oven at 70°C, and then calcine at 300°C to 400°C in an air atmosphere to obtain a rod-shaped nano copper oxide powder with a high aspect ratio; the rod-shaped nano copper oxide with a high aspect ratio has a length of 5 to 10 μm, a diameter of 30 to 60 nm, and an average aspect ratio of about 150:1. The SEM image of the rod-shaped nano copper oxide with a high aspect ratio obtained in this manner can be referred to Figure 2 As shown, the XRD pattern of the high aspect ratio rod-shaped nano copper oxide obtained by this method can be referred to Figure 3 shown.
[0066] The copper salt aqueous solution in step 1 of this embodiment can also be replaced by copper sulfate, copper nitrate or copper chloride; the mixed alkaline solution can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or other mixtures in ammonia.
[0067] Example 2
[0068] The preparation method of this embodiment comprises the following steps:
[0069] Step 1, preparing copper acetate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and a mixed alkaline solution respectively; the concentration of the copper salt aqueous solution is 70 g / L, the concentration of sodium carbonate in the mixed alkaline solution is 100 g / L, the concentration of sodium hydroxide is 40 g / L, and the pH value of the mixed alkaline solution is between 12 and 14, which is in a strong alkaline state;
[0070] Step 2: With the aid of a high-frequency ultrasonic dispersion device having a frequency of 4 MHz, a copper salt aqueous solution is gradually added to a sodium hydroxide-sodium carbonate alkaline mixed solution to prepare a copper-mixed alkaline solution;
[0071] Step 3: Transfer the copper-mixed alkali solution obtained in step 2 to a polytetrafluoroethylene reactor, adopt a hydrothermal synthesis method, the reaction temperature is 120° C., the pressure in the reactor is between 3 and 10 MPa, and after four hours, collect and obtain a nanoparticle solution containing copper compounds;
[0072] Step 4: centrifuge the copper compound nanoparticle solution collected in step 3, wash with 18.2MΩ ultrapure water, dry in an oven at 70°C, and then calcine at 300°C to 400°C in an air atmosphere to obtain a rod-shaped nano copper oxide powder with a high aspect ratio; the rod-shaped nano copper oxide with a high aspect ratio has a length of 5 to 20 μm, a diameter of 30 to 100 nm, and an average aspect ratio of about 200:1.
[0073] The copper salt aqueous solution in step 1 of this embodiment can also be replaced by copper sulfate, copper nitrate or copper chloride; the mixed alkaline solution can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or other mixtures in ammonia.
[0074] Example 3
[0075] The preparation method of this embodiment comprises the following steps:
[0076] Step 1, preparing copper acetate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and a mixed alkaline solution respectively; the concentration of the copper salt aqueous solution is 70 g / L, the concentration of sodium carbonate in the mixed alkaline solution is 100 g / L, the concentration of sodium hydroxide is 40 g / L, and the pH value of the mixed alkaline solution is between 12 and 14, which is in a strong alkaline state;
[0077] Step 2: With the aid of a high-frequency ultrasonic dispersion device having a frequency of 4 MHz, a copper salt aqueous solution is gradually added to a sodium hydroxide-sodium carbonate alkaline mixed solution to prepare a copper-mixed alkaline solution;
[0078] Step 3: Transfer the copper-mixed alkali solution obtained in step 2 to a polytetrafluoroethylene reactor, adopt a hydrothermal synthesis method, the reaction temperature is 120° C., the pressure in the reactor is between 3 and 10 MPa, and collect the nanoparticle solution containing the copper compound after one hour;
[0079] Step 4: centrifuge the copper compound nanoparticle solution collected in step 3, wash it with 18.2MΩ ultrapure water, freeze it, and then calcine it at 300°C to 400°C in an air atmosphere to obtain a rod-shaped nano copper oxide powder with a high aspect ratio; the rod-shaped nano copper oxide with a high aspect ratio has a length of 1 to 5 μm, a diameter of 10 to 50 nm, and an average aspect ratio of about 100:1.
[0080] The copper salt aqueous solution in step 1 of this embodiment can also be replaced by copper sulfate, copper nitrate or copper chloride; the mixed alkaline solution can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or other mixtures in ammonia.
[0081] Comparative Example 1
[0082] The preparation method of this embodiment comprises the following steps:
[0083] Step 1, preparing copper acetate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and a mixed alkaline solution respectively; the concentration of the copper salt aqueous solution is 70 g / L, the concentration of sodium carbonate in the mixed alkaline solution is 100 g / L, the concentration of sodium hydroxide is 40 g / L, and the pH value of the mixed alkaline solution is between 12 and 14, which is in a strong alkaline state;
[0084] Step 2: Adding a copper salt aqueous solution to a sodium hydroxide-sodium carbonate alkaline mixed solution with the aid of a high-frequency ultrasonic dispersion device with a frequency of 4 MHz to prepare a copper-mixed alkaline solution;
[0085] Step 3: Transfer the copper-mixed alkali solution obtained in step 2 to a polytetrafluoroethylene reactor, adopt a hydrothermal synthesis method, the reaction temperature is 130° C., the pressure in the reactor is between 3 and 10 MPa, and after two hours, collect and obtain a nanoparticle solution containing copper compounds;
[0086] Step 4: Centrifuge the copper compound nanoparticle solution collected in step 3, wash with 18.2MΩ ultrapure water, dry in an oven at 70°C, and then calcine at 300°C to 400°C in an air atmosphere to obtain a rod-shaped nano copper oxide powder with a high aspect ratio; the rod-shaped nano copper oxide with a high aspect ratio has a length of 1 to 10 μm, but is accompanied by a small amount of agglomeration. The SEM image of the rod-shaped nano copper oxide obtained in this way can be referred to Figure 4 shown.
[0087] The copper salt aqueous solution in step 1 of this comparative example can also be replaced by copper sulfate, copper nitrate or copper chloride; the mixed alkaline solution can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or other mixtures in ammonia.
[0088] Comparative Example 2
[0089] The preparation method of this embodiment comprises the following steps:
[0090] Step 1, preparing copper acetate, sodium carbonate and sodium hydroxide into a copper salt aqueous solution and a mixed alkaline solution respectively; the concentration of the copper salt aqueous solution is 70 g / L, the concentration of sodium carbonate in the mixed alkaline solution is 100 g / L, the concentration of sodium hydroxide is 40 g / L, and the pH value of the mixed alkaline solution is between 12 and 14, which is in a strong alkaline state;
[0091] Step 2: Adding a copper salt aqueous solution to a sodium hydroxide-sodium carbonate alkaline mixed solution with the aid of a high-frequency ultrasonic dispersion device with a frequency of 4 MHz to prepare a copper-mixed alkaline solution;
[0092] Step 3: Transfer the copper-mixed alkali solution obtained in step 2 to a polytetrafluoroethylene reactor, adopt a hydrothermal synthesis method, the reaction temperature is 140° C., the pressure in the reactor is between 3 and 10 MPa, and after two hours, collect and obtain a nanoparticle solution containing copper compounds;
[0093] Step 4: centrifuge the copper compound nanoparticle solution collected in step 3, wash with 18.2MΩ ultrapure water, dry in an oven at 70°C, and then calcine at 300°C to 400°C in an air atmosphere to obtain a rod-shaped nano copper oxide powder with a high aspect ratio; the rod-shaped nano copper oxide with a high aspect ratio has a length of 3 to 6 μm, but is completely agglomerated into large pieces. The SEM image of the nano copper oxide obtained in this way can be referred to Figure 5 shown.
[0094] The copper salt aqueous solution in step 1 of this comparative example can also be replaced by copper sulfate, copper nitrate or copper chloride; the mixed alkaline solution can also be replaced by sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate or other mixtures in ammonia.
[0095] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.
[0096] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.
[0097] It should be understood that the present disclosure is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims. The description and embodiments are to be regarded as exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.
Claims
1. A method for preparing copper nanorods, characterized in that: The method comprises the following steps: Step 1: preparing a copper salt into a copper precursor aqueous solution, and preparing a base into an alkaline mixed solution; Step 2: adding the copper precursor aqueous solution to the alkaline mixed solution under the assistance of ultrasound to obtain a copper-mixed alkaline solution; Step 3, transferring the copper-mixed alkali solution to a polytetrafluoroethylene reactor for hydrothermal reaction to obtain a nanoparticle solution containing copper compounds; Step 4: solid-liquid separation, washing, drying and calcining of the nanoparticle solution containing copper compound to obtain copper oxide powder composed of rod-shaped nano copper oxide.
2. The method for preparing copper nanorods according to claim 1, characterized in that: The copper salt includes at least one of copper chloride, copper acetate, copper sulfate and copper nitrate, The concentration of the copper precursor aqueous solution is less than or equal to 70 g / L.
3. The method for preparing copper nanorods according to claim 1, characterized in that: The alkaline mixed solution includes multiple ones of sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonium carbonate, ammonium bicarbonate and ammonia water. The concentration of the alkaline mixed solution is less than or equal to 150g / L. The pH value of the alkaline mixed solution is between 12 and 14, which is in a strong alkaline state.
4. The method for preparing copper nanorods according to claim 3, characterized in that: The alkaline mixed solution includes any one of the following: a mixed solution of sodium hydroxide and sodium carbonate, a mixed solution of sodium hydroxide and sodium bicarbonate, a mixed solution of sodium hydroxide and ammonium carbonate, a mixed solution of sodium hydroxide and ammonium bicarbonate, and a mixed solution of sodium hydroxide and aqueous ammonia.
5. The method for preparing copper nanorods according to claim 1, characterized in that: In the ultrasonic-assisted scenario, the frequency of the ultrasonic wave is less than or equal to 4 MHz; In the process of adding the copper precursor aqueous solution into the alkaline mixed solution, the adding method adopted is any one of dripping, peristaltic pump injection and atomization spraying.
6. The method for preparing copper nanorods according to claim 1, characterized in that: In the process of transferring the copper-mixed alkali solution to the polytetrafluoroethylene reactor for hydrothermal reaction, the temperature of the hydrothermal reaction is 100° C. to 200° C., and the duration of the hydrothermal reaction is 1 to 10 hours; During the process of transferring the copper-mixed alkali solution to the polytetrafluoroethylene reactor for hydrothermal reaction, the pressure in the polytetrafluoroethylene reactor is between 3 and 10 MPa.
7. The method for preparing copper nanorods according to claim 1, characterized in that: In the process of solid-liquid separation of the nanoparticle solution containing the copper compound, the solid-liquid separation method includes centrifugal separation or suction filtration separation; In the process of washing the copper-containing compound nanoparticles after solid-liquid separation, the washing solution used includes water or ethanol; In the process of drying the washed copper compound-containing nanoparticles, the drying method used includes heat drying or cold drying; In the process of calcining the dried copper-containing compound nanoparticles, the calcination temperature used is 200°C to 500°C.
8. The method for preparing copper nanorods according to claim 1, characterized in that: During the calcination of the dried copper-containing compound nanoparticles, the atmosphere used is air.
9. The copper nanorods obtained by the method for preparing copper nanorods according to any one of claims 1 to 8, characterized in that: The copper nanorods are rod-shaped nano copper oxides with a high aspect ratio. The rod-shaped nano copper oxides with a high aspect ratio have a length of 5 to 10 μm, a diameter of 30 to 60 nm, and an average aspect ratio of 100 to 200:
1.
10. The copper nanorod according to claim 9, characterized in that: The rod-shaped nano-copper oxide with a high aspect ratio is used to prepare electronic devices and / or sensors.